Role of seeding rate and variety in increasing yield performance and weed suppressing ability of wheat under strip tillage system - Zahan, Taslima; Rahman, Md Moshiur; Bell, Richard W; Haque, Md Enamul (Fundamental and Applied Agriculture, 2017)
Mechanical seeding of wheat under strip tillage system is time demanding technique that necessitates adjustment of the appropriate seeding rate for different wheat varieties to achieve optimum yield. However, high weed pressure is considered as a major cause of wheat yield loss in strip tillage system and hence an assessment needs to be carried out on integrated management approach to suppress weeds. Therefore, a study was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh during November 2012–March 2013 to examine the effect of seeding rate and variety on weed suppression and yield performance of wheat under strip tillage system. Three wheat varieties (BARI Gom-21, BARI Gom-24 and BARI Gom-26) were evaluated in the study with five seeding rates (40, 60, 80, 100 and 120 kg ha-1) following a split-plot design with three replications. The study revealed that seeding rate and variety had significant effect on weed and yield of wheat under strip tillage system. Seeding at the rate of 120 kg ha-1 offered the highest weed suppression with the highest wheat yield. Among the varieties, BARI Gom-21 provided the superior performance on weed suppression and produced higher yield. The lowest grain and straw yields were obtained from BARI Gom-24 at 40 kg ha-1 seed rate with lowest weed suppression. The study concluded that mechanical seeding of BARI Gom-21 at the rate of 120 kg ha-1 was the best under strip tillage system that ensured maximum wheat yield with successful weed suppression.